Examining the Impact of Training Practices and Organizational Culture on Police Misconduct in Law Enforcement Agencies in the Regional Training Center 5 - Benjamin Custodio (Philippine Association of Institutions for Research, Inc., 2023)
This study investigates the relationship between training practices, organizational culture, incidents of abuse of authority, and unsafe training practices within law enforcement agencies. The main purpose of the study is to identify factors contributing to police misconduct and to provide recommendations for reforms to ensure the safety and well-being of trainees, prevent similar incidents in the future, and restore public faith in law enforcement agencies. This study used a combination of qualitative and quantitative methodology. The quantitative method was used to get the data from surveys coming from the participants and official records from the involved agency and organization. The qualitative method was used for the interviews and case studies. The sample includes trainees, officers, and supervisors from various law enforcement agencies. Results reveal that abuse of authority and unsafe training practices are associated with a negative organizational culture, inadequate ethical training, and a lack of effective leadership. Furthermore, the fear experienced by trainees in complying with excessive demands contributes to the risk of harm. The study also found that such incidents can damage the reputation of the police force, leading to a loss of public trust and confidence. In conclusion, the findings emphasize the need for a comprehensive approach to address these issues, including implementing ethical training, strong leadership, transparency, accountability measures, and evidence-based recruitment practices. These measures can promote a positive organizational culture, enhance the safety and well-being of trainees, and restore public faith in law enforcement agencies.